Race, resistance, and the Boy Scout movement in British Colonial Africa - Parsons, Timothy, 1962- (Ohio University Press, 2004)
Conceived by General Sir Robert Baden-Powell as a way to reduce class tensions in Edwardian Britain, scouting evolved into an international youth movement. It offered a vision of romantic outdoor life as a cure for disruption caused by industrialization and urbanization. Scouting''s global spread was due to its success in attaching itself to institutions of authority. As a result, scouting has become embroiled in controversies in the civil rights struggle in the American South, in nationalist resistance movements in India, and in the contemporary American debate over gay rights.